The Expression of Sterigmatocystin and Penicillin Genes in Aspergillus nidulans Is Controlled by veA, a Gene Required for Sexual Development - Kato, Naoki (American Society for Microbiology, 2003)
Secondary metabolism is commonly associated with morphological development in microorganisms, including fungi. We found that veA, a gene previously shown to control the Aspergillus nidulans sexual/asexual developmental ratio in response to light, also controls secondary metabolism. Specifically, veA regulates the expression of genes implicated in the synthesis of the mycotoxin sterigmatocystin and the antibiotic penicillin. veA is necessary for the expression of the transcription factor aflR, which activates the gene cluster that leads to the production of sterigmatocystin. veA is also necessary for penicillin production. Our results indicated that although veA represses the transcription of the isopenicillin synthetase gene ipnA, it is necessary for the expression of acvA, the key gene in the first step of penicillin biosynthesis, encoding the delta-(l-alpha-aminoadipyl)-l-cysteinyl-d-valine synthetase. With respect to the mechanism of veA in directing morphological development, veA has little effect on the expression of the known sexual transcription factors nsdD and steA. However, we found that veA regulates the expression of the asexual transcription factor brlA by modulating the α/β transcript ratio that controls conidiation.